Maqāshid Syari’ah Correlation and Good Corporate Governance in Pawnshop Syarī’ah Companies - Pandu Bagus Prakoso; Angger Supriyatno; Mohamad Djasuli (Al-Widad, 2022)
This study aims to describe the relationship between maqāshid syari’ah and Good Corporate Governance in sharia pawnshops as a performance implementation in realizing prosperity and avoiding social inequality so that it can solve the poverty problem in people’s lives. This research methodology uses a qualitative approach with the type of library research, in which data collection is carried out by analyzing various existing literature and regulations and laws, which are then described. The findings and results of this study; the concept of maqāshid syarī’ah must always be applied so that it is by good corporate governance in good corporate governance; pawnshop syarī’ah companies must embody the concept of maqāshid syarī’ah so that social inequality and poverty no longer exist in people’s lives because the purpose of implementing Islamic law is to guard the soul, religion, mind, lineage and wealth. Socio-economic justice in the study of Islamic studies must always prioritize the interests and benefits of the general public.